2013
DOI: 10.1056/nejmoa1300799
|View full text |Cite
|
Sign up to set email alerts
|

Use of Azithromycin and Death from Cardiovascular Causes

Abstract: Azithromycin use was not associated with an increased risk of death from cardiovascular causes in a general population of young and middle-aged adults. (Funded by the Danish Medical Research Council.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
173
3
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(185 citation statements)
references
References 15 publications
4
173
3
5
Order By: Relevance
“…30 More than one million health visits with prescription of azithromycin were matched (by propensity scores, to control for baseline dif ferences) with a similar number of visits without prescription of antibiotics and with about seven million visits with prescription of penicillin V. Although there were more deaths from cardio vascular causes in the azithromycin group than in the nonantibiotic group (rate ratio 2.85, 95% CI 1.13-7.24), this rate was not significantly dif ferent from the rate in the penicillin V group (rate ratio 0.93, 95% CI 0.56-1.55). This result suggests that the difference in cardiovascular deaths was related to other characteristics, such as comorbidities, among the patients receiving antibiotics, rather than a specific risk associated with azithromycin.…”
Section: What Are the Potential Harms Of Long-term Macrolide Therapy mentioning
confidence: 99%
“…30 More than one million health visits with prescription of azithromycin were matched (by propensity scores, to control for baseline dif ferences) with a similar number of visits without prescription of antibiotics and with about seven million visits with prescription of penicillin V. Although there were more deaths from cardio vascular causes in the azithromycin group than in the nonantibiotic group (rate ratio 2.85, 95% CI 1.13-7.24), this rate was not significantly dif ferent from the rate in the penicillin V group (rate ratio 0.93, 95% CI 0.56-1.55). This result suggests that the difference in cardiovascular deaths was related to other characteristics, such as comorbidities, among the patients receiving antibiotics, rather than a specific risk associated with azithromycin.…”
Section: What Are the Potential Harms Of Long-term Macrolide Therapy mentioning
confidence: 99%
“…9 In the first 5 days of therapy, there were 17 cardiovascular deaths among the 1 102 050 episodes of azithromycin use and 146 cardiovascular deaths among the 7 364 292 episodes of penicillin V use (rate ratio 0.93, 95% confidence interval [CI] 0.56-1.55). However, this patient population differed from the patients in the study by Ray and others.…”
Section: Resultsmentioning
confidence: 99%
“…Case reports of torsades de pointes associated with azithromycin have been published, and AZCERT (an independent nonprofit organization with a mandate to provide credible information on drugs that prolong the QT interval) now lists it as a medication with substantial evidence that it causes this problem. [7][8][9] A recent retrospective cohort study using the Tennessee Medicaid database reported an increase in cardiovascular mortality associated with azithromycin use. 10 In that study, a cohort of patients who took azithromycin was compared with a propensity score-matched cohort of patients who took no antibiotics.…”
Section: Is Azithromycin Safe To Use In the Treatment Of Cap?mentioning
confidence: 99%
“…В наблюдательном исследовании, объ единившем > 1 млн случаев приема азитромицина, у получавших этот препарат чаще развивались фа тальные аритмии по сравнению с больными, не при нимавшими его (отношение рисков (ОР) -2,85; 95% ный ДИ -1,13-7,24) [118]. Абсолютный риск фатальных нарушений сердечного ритма на фоне те рапии азитромицином невелик (1,1 случая на 1 000 пациенто лет) и он не превышает аналогичный риск, связанный с приемом других антибактериаль ных препаратов (ОР -0,93; 95% ный ДИ -0,56-1,55) [118]. Эти результаты подтверждены в другом исследовании, выполненном производителями азит ромицина [119].…”
Section: рекомендацияunclassified